Pengaruh Hidroterapi Terhadap Penurunan Gula Darah Sewaktu (GDS) pada Pasien Diabetes Mellitus Tipe II - Kurniasari, Septi; Sriningsih, Nining; Antoro, Budi; Efrifahrizal, Hengky (An Idea Nursing Journal, 2023)
Cases of DM in Indonesia in 2019 there were 8.426.000, and this quantity is expected to increase to 21,257,000 in 2030. At the Sukabumi Health Center in Bandar Lampung, there were 668 cases of diabetes. Alternative and complementary therapies are efforts that can be made to manage hyperglycemia. Hydrotherapy is a complementary treatment that can be used by type 2 diabetics to treat hyperglycemia. The purpose of this research was to find out how hydrotherapy affects the ability of type 2 diabetes mellitus patients to gradually lower blood sugar levels (KGDS). This kind of exploration is a quantitative report, using a semi-exploration plan. A pre-test-posttest design with a control group was used for the study. The participants of this study were all type II diabetics who went to the Sukabumi Health Center in Bandar Lampung. In May 2019, 58 people participated, bringing the sample to 36 people. Glucotest was used for data collection, Independent T-test was used for bivariate and univariate analysis. The results showed that the intervention group who received hydrotherapy experienced an average decrease in blood sugar levels of 52.5 mmHg, while the control group who received treatment experienced an average decrease in blood sugar levels of 33.56. At the Sukabumi Health Center in Bandar Lasmpung in 2020, statistical tests yielded a value of 0.001 (P value = 0.001, where the P value was (0.05), indicating that hydrotherapy has an effect on a decrease in blood sugar levels over time (KGDS) in patients with type 2 diabetes. Health education banners and flyers are expected to be distributed to promote hydrotherapy as a more effective way to lower blood sugar levels.